Rancang Bangun Mobile Robot Micromouse Untuk Pencarian Rute Terpendek Menggunakan Algoritma Flood Fill - Werman Kasoep (Universitas Andalas, 2017)
Mobile Robot is one robot that much used to help out man. Micromouse mobile robot is one robot that made to can find the route shortest in a maze. Flood fill algorithm is one way to find the route shortest by doing maze mapping, where the robot will compare the value of each cell and moving toward the smallest cell. In the research, the micromouse mobile robot was designed using Ultrasonic PING sensor to detect obstacles and Arduino Uno that will control the movement of DC motor. The robot will search a route shortest based on maze mapping that it has passed. The robot was tested on three mazes, where each maze was tested 10 times and obtained success level on the first maze of 80%, the second maze of 70% and the third maze of 70%.